THE DEVELOPMENT OF NEUROSCAFFOLD FOR THE GLIOBLASTOMA THERAPY - Yu. S. Maklygina; A. S. Sharova; A. V. Borodkin; G. M. Yusubalieva; A. V. Ryabova; D. V. Pominova; E. A. Lukyanets; S. A. Goryainov; A. A. Potapov; V. P. Chekhonin; I. A. Shcherbakov; V. B. Loshchenov (Biomedical Photonics, 2018)
Current paper presents the results of the system development for intracranial implantation aimed on therapy and prevention of brain gliomas relapse. The main property of the system, in prospective,  will be to direct the growth of glioma cells localized in the region  adjacent to the site of the removed tumor along the fi bers towards  the proximal part of the fiber-optic scaffold (neuroport). Such  approach will allow carrying out cells diagnostics by the  photoluminescence signal and provide subsequent destruction of  malignant cells by photodynamic action. Besides, this system could  be used for monitoring the processes occurring in the probed area in order to control the possible relapses. The localization of cells along  the fi ber structures covered with gelatin compound, which is the  source of amino acids during cultivation, was shown during the glioma cells growth dynamics study. Moreover, four different designs of intracranial scaffold models, serving as ports for diagnostic and therapeutic laser radiation delivery, were developed and  successfully tested in the framework of the research. The results  obtained on the rats brain with induced tumors (glioma C6) after  neuroport implantation demonstrate sufficiently intense fluorescence in the tumor bed after intravenous injection of the  nonmetallic sulfonated phthalocyanine based photosensitizer, and a  pronounced photodynamic effect leading to total destruction of the  tumor. In this way, the results of this study open the prospects of creating the neuroport with an internal fi ber structure that focuses the glioma cells growth.